Pyrethroid insecticides in wild bird eggs from a World Heritage Listed Park: A case study in Doñana National Park (Spain). (September 2017) - Corcellas, Cayo; Andreu, Ana; Máñez, Manuel; Sergio, Fabrizio; Hiraldo, Fernando; Eljarrat, Ethel; Barceló, Damià
Abstract: Recent studies demonstrated that the common pyrethroid insecticides are present in aquatic biota tissues. In this study, 123 samples of unhatched eggs of 16 wild bird species collected from 2010 to 2012 in Doñana National and Natural Park were analysed to determine 13 pyrethroids. This study represents the first time that pyrethroids are detected in tissues of terrestrial biota, 93% of these samples being positive to those pollutants. Levels of total pyrethroids ranged from not detected to 324 ng g −1 lw. The samples were characterized by stable isotope analysis. Species with diets based on anthropogenic food showed higher levels of pyrethroids and lower values of δ 15 N. Finally, we characterized the isomers of pyrethroids and discerned some isomeric- and enantiomeric-specific accumulations. In particular, tetramethrin and cyhalothrin showed an enantiomeric-selective accumulation of one enantiomer, highlighting the need to assess toxicological effects of each enantiomer separately to be able to make a correct risk assessment of pyrethroids in birds. Graphical abstract: Highlights: 93% of wild bird eggs analysed showed pyrethroid levels, up to 324 ng g −1 lw. Cypermethrin, cyhalothrin and bifentrhin were the most ubiquitous pyrethroids, being present in more than 77% of samples. Urban areas are the main source of pyrethroid contamination in wild bird eggs. Some isomeric- and enantiomeric-specific accumulation of pyrethroids has been observed. Abstract : Pyrethroid insecticides were found for the first time in wild bird eggs.